2016
DOI: 10.1002/2015ja022264
|View full text |Cite
|
Sign up to set email alerts
|

ELF/VLF wave propagation at subauroral latitudes: Conjugate observation between the ground and Van Allen Probes A

Abstract: We report simultaneous observation of ELF/VLF emissions, showing similar spectral and frequency features, between a VLF receiver at Athabasca (ATH), Canada, (L = 4.3) and Van Allen Probes A (Radiation Belt Storm Probes (RBSP) A). Using a statistical database from 1 November 2012 to 31 October 2013, we compared a total of 347 emissions observed on the ground with observations made by RBSP in the magnetosphere. On 25 February 2013, from 12:46 to 13:39 UT in the dawn sector (04–06 magnetic local time (MLT)), we o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 41 publications
5
54
0
Order By: Relevance
“…However, the generation mechanism of QP emissions based on ULF magnetic field pulsations could possibly explain the time delay of about 15 s between individual QP elements detected by the THEMIS E and RBSP spacecraft. Time delays on the order of a few seconds might possibly result from the whistler mode wave propagation [ Němec et al , ; Martinez‐Calderon et al , ]. However, the whistler wave propagation is too fast and the observed time delays, particularly well seen in the time interval 01:05–01:15 UT, is too large for such an explanation to be used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the generation mechanism of QP emissions based on ULF magnetic field pulsations could possibly explain the time delay of about 15 s between individual QP elements detected by the THEMIS E and RBSP spacecraft. Time delays on the order of a few seconds might possibly result from the whistler mode wave propagation [ Němec et al , ; Martinez‐Calderon et al , ]. However, the whistler wave propagation is too fast and the observed time delays, particularly well seen in the time interval 01:05–01:15 UT, is too large for such an explanation to be used.…”
Section: Discussionmentioning
confidence: 99%
“…When the observations are made at nearly the same magnetic local times (MLTs) but separated radially by about 0.5 R E , the observed time delays are on the order of a couple of seconds. This can be likely explained by the unducted wave propagation from the source region located at larger radial distances [ Němec et al , ; Martinez‐Calderon et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…Their link with geomagnetic pulsations suggests that their periodicity is related to modulation by ultra low frequency waves (e.g., Morrison, 1990;Nėmec et al, 2013;Sato & Fukunishi, 1981;Sato & Matsudo, 1986). In this paper, we define a conjugate event as the simultaneous observation of the same wave on the ground and in space, indicating that we are observing waves from the same geomagnetic source (Martinez-Calderon, 2016). However, QP observations are not necessarily accompanied by geomagnetic pulsations; thus, another explanation for their generation is related to auto-oscillations of the cyclotron instability of the Earth radiation belts (Trakhtengerts & Rycroft, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Nėmec et al (2016) show that the time delay between QP simultaneously detected in space and on the ground is related to azimuthally propagating compressional ultra low frequency waves responsible for the generation of the QP. Although by their nature, conjugated events give us significant information on the generation and propagation of waves, up until now they remain rare with only a handful of documented cases (Martinez-Calderon, 2016;Nėmec et al, 2016;Titova et al, 2015). Manninen et al (2013) and Manninen et al (2014) found that the variations of QP periods, particularly their gradual increment, can be explained by the auto-oscillation regime of the cyclotron instability in the magnetosphere.…”
Section: Introductionmentioning
confidence: 99%
“…In the PWING project, we expect to use quite a uniform dataset for comparison of the waves at different local times. Comparison with Arase and Van Allen Probes also provides important information on the propagation of magnetospheric ELF/VLF waves to the ground (e.g., Martinez-Calderon et al 2016).…”
Section: Frequency [Hz]mentioning
confidence: 99%